Androgen Receptor Gene CAG Repeat Polymorphism Regulates the Metabolic Effects of Testosterone Replacement Therapy in Male Postsurgical Hypogonadotropic Hypogonadism - Giacomo Tirabassi; Nicola delli Muti; Giovanni Corona; Mario Maggi; Giancarlo Balercia (International Journal of Endocrinology)
Aim. To evaluate the independent role of androgen receptor (AR) gene CAG repeat polymorphism on metabolic effects of testosterone replacement therapy (TRT) in male postsurgical hypogonadotropic hypogonadism, a condition frequently associated with hypopituitarism and in which the TRT-related metabolic effects are combined with those deriving from concomitant administration of metabolically active pituitary-function replacement therapies. Methods. 15 men affected by postsurgical hypogonadotropic hypogonadism were evaluated before and after TRT. Cardiovascular risk factors (CVRFs), pituitary-dependent hormones, and AR gene CAG repeat polymorphism were considered. Results. Testosterone, insulin-like growth factor 1 (IGF-1), and estradiol were the only hormones, which varied significantly between the two phases. All CVRFs significantly improved after TRT. The number of CAG triplets was positively and significantly correlated with all the variations (Δ-) of CVRFs (except for a significant negative correlation with Δ-high-density lipoprotein); the opposite occurred between the latter and Δ-testosterone. No correlation between Δ-IGF-1 or estradiol and Δ-CVRFs was found. At multiple linear regression, after correction for Δ-testosterone, nearly all the associations between the number of CAG triplets and Δ-CVRFs were confirmed. Conclusions. In male postsurgical hypogonadotropic hypogonadism, shorter AR gene CAG tract length seems to yield greater metabolic improvement after TRT, independently of the effects of concomitant pituitary-function replacement therapies.